Study of the 193Ir(n,2n)192Ir Reaction Cross Section - Patronis, N.; Kalamara, A.; Harissopulos, S.; Kokkoris, M.; Lagoyannis, A.; Vlastou, R. (HNPS Advances in Nuclear Physics, 2019)
The 193Ir(n,2n)192Ir reaction cross section was measured relative to the 27Al(n,a)24Na and 197Au(n,2n)196Au reactions by means of the activation technique at two neutron beam energies: 10.0 and 10.5 MeV. The neutron beam was produced via the 2H(d,n)3Ηe reaction. The deuteron beam was provided by the 5.5 MV Tandem Van de Graaff accelerator of the N.C.S.R. “Demokritos”. After the irradiations the induced activity of the samples was measured through a 56% relative efficiency HPGe detector. The total reaction cross section for the population of the ground state (4+) and the first isomeric state (1-) was determined. The adopted method for the correction concerning the population of the product nucleus 192Ir through the 191Ir(n,γ)192Ir reaction is also presented.